(untitled) (Global Journal of Medical Research, 2020)
African swine fever (ASF) outbreaks have been reported in Sub-Saharan countries, including West Africa states, but has never been notified in the Republic of Sierra Leone. This is the first report describing field epidemiological and laboratory investigations into the outbreak of fatal pig disease in western rural and urban districts, Freetown. A preliminary finding indicated that pigs exhibited clinical and necropsy signs suggestive of ASF. Serological (ELISA) and molecular (qRT-PCR) methods used to confirm and investigate the outbreak yielded three positive results for the ASF antibody and all negative for Swine flu; thus, confirming ASF as the etiology agent.